Palynostratigraphy of the lower Paleogene Margaret Formation at Stenkul Fiord, Ellesmere Island, Nunavut, Canada. (3rd July 2021) - Sudermann, Markus; Galloway, Jennifer M.; Greenwood, David R.; West, Christopher K.; Reinhardt, Lutz
Abstract: The upper Paleocene to lower Eocene Margaret Formation exposed at Stenkul Fiord on southern Ellesmere Island, Nunavut, Canada, represents a nearly continuous terrestrial succession of microfossil-rich clastic sediments and coal. These strata were deposited at a time of extensive tectonic activity associated with Eurekan deformation. The precise chronology of the Eurekan deformation is poorly known. Prior studies at Stenkul Fiord provided a stratigraphic overview and relative age estimates for exposed strata but lack the absolute age control required to investigate the timing of deformation events. Strata at Stenkul Fiord preserve evidence of Arctic forests that may have grown during hyperthermal events that characterized the Paleogene, namely, the Paleocene-Eocene Thermal Maximum (PETM) and Eocene Thermal Maximum 2 (ETM2). A quantitative palynological approach is herein used to define a new higher-resolution biostratigraphic framework for the Margaret Formation strata at Stenkul Fiord. This resulting improved biostratigraphic framework is integrated with new absolute age control of 53.7 ± 0.06 Ma provided by U-Pb ID-TIMS of zircon preserved in an ash bed within the studied succession. Nine pollen zones are defined based on cluster analysis, NMDS ordination, first- and last occurrences of taxa, and angiosperm pollen taxa diversity ( H ′). The presence of thermophilic pollen taxa at Stenkul Fiord provides evidence of climates related to the globally warm climates during the early Paleogene.